Effects of Plyometric Training on Grass Surface and Concrete Surface on Jumping Performance Among Volleyball Athletes - Mohamad Hariff, Ramlan (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2018)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe